Phytochemical characterization of ethanolic and ethyl acetate extracts of avocado Persea americana leaves by FT-IR and GC-MS reveals potential bioactive compounds - Mary Olaoluwa Agunloye; Daniel. U. Owu; Olufunke Onaadepo; Felix Nnaemeka Ugwu; Oludare Michael Ogunyemi (Scientific Reports)
Abstract Persea americana (avocado) is widely recognized for its nutritional and therapeutic value; however, its leaves, abundant and often discarded, remain underexplored. With growing interest in plant-derived bioactives, comprehensive phytochemical profiling of avocado leaves is essential to validate their pharmacological and nutraceutical potential. Fresh leaves of P. americana collected in Uganda were shade-dried and extracted by cold maceration using ethanol and ethyl acetate. Phytochemical characterization was conducted using Fourier-transform infrared spectroscopy (FT-IR) to identify functional groups and gas chromatography-mass spectrometry (GC-MS) to detect bioactive constituents. Extraction conditions and analytical parameters were optimized for reproducibility. FT-IR spectra revealed functional groups characteristic of phenolics, flavonoids, terpenoids, and esters, including hydroxyl (–OH), carbonyl (C=O), alkenes (C=C), aromatic (C–H), methylene (C–H₂), methyl (C–H₃), and esters (C–O). GC-MS showed distinct solvent-dependent profiles: the ethanolic extract (PA-ETH) contained major compounds such as 13-Octadecenal (35.90%), Hexadecanoic acid, methyl ester (10.50%), and linoleic acid ethyl ester (7.02%), noted for antioxidant and cardioprotective properties. The ethyl acetate extract (PA-ETHYL) exhibited higher compound diversity, including 9,12-Octadecadienoic acid (Z,Z)- (1.12%), 2,6,10-Dodecatrien-1-ol, 3,7,11-trimethyl-, (Z,E)- (12.31%), and Caryophyllene oxide (1.48%), linked to anti-inflammatory, Hypocholesterolemic, and anticancer activities. Notably, some compounds with no previously reported pharmacological activity may represent novel bioactives. Solvent polarity significantly influenced phytochemical composition, with ethanol favoring polar antioxidants and ethyl acetate enhancing extraction of non-polar bioactives. This study highlights the therapeutic promise of P. americana leaves and establishes a robust chemical foundation for future bioactivity-guided isolation, pharmacological validation, and natural product drug discovery.